Cognitive processes in social phobia. - Stopa, L; Clark, D (1993)
Social phobics, anxious controls and non-patient controls took part in a brief videotaped conversation with a stooge in order to investigate the cognitive model of social phobia. Thoughts, behaviour, and attention during the conversation were assessed. Compared to the control groups, social phobics had more negative self-evaluative thoughts, performed less well, and systematically underestimated their performance. There were no differences in attention between the three groups. Content analysis of thought sampling data from the conversation, and from three hypothetical situations, revealed that few of the negative thoughts reported by social phobics explicitly mentioned evaluation by other people. This suggests that social phobics may not closely monitor other people's responses in social situations and hence that their thoughts are not data driven. The results are discussed in relation to the cognitive model of social phobia and suggestions are made for improvements in the treatment of social phobia.